Effect of temperature and heat treatment on physical properties and finishing quality of mahagony wood - Ragil Widyorini; Khusnul Khotimah; Tibertius Agus Prayitno (Jurnal Ilmu Kehutanan)
Heat treatment is well known as a method for increasing dimensional stability and reducing hygroscopicity of wood. However, heat tratment can cause the color of wood become darker and reduce the wettability, as well as its mechanical properties. Therefore, the optimum condition of heat treatment is essential to be studied to obtain the high quality of properties treated wood. This research focused on investigating the heating temperature and treatment method on physical properties and finishing quality of mahagony wood. Two treatment methods, i.e. oven method and steaming method, were used in this research. The heating temperatures were set at 90°C, 120°C, and 150°C. The effective heating time was 2 h. The wood physical properties were tested according to ASTM standards and wood finishing quality were tested for its cross cut, delamination, and glossy test. The results showed that interaction between treatment method and heating temperature affected significantly on the change in color, radial shrinkage, cross cut test, and delamination test. Oven method resulted in reducing moisture content and radial shrinkage, light color, and better quality of wood, compared to steaming method.